(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2007)
A highly stable, low noise 10.7 GHz frequency synthesizer for radio-relay link transceiver is presented. The basic elements of synthesizer are electrically tuned 5.35 GHz dielectric ring oscillator and transistor frequency doubler.